An aging cyclists time trial performances over four decades: A case study - Dyer, B. (Journal of Science and Cycling, 2020)
Previous research has often highlighted the physiological decline an athlete will be subjected to as they age. However, whilst some studies has evaluated a large sample of athletes at a given age, few studies have evaluated a single athlete over a much longer period of time in sports such as cycling. This study assessed the time trial performances of a multiple national record holding male amateur cyclist from when they were aged between 37 to 75 years of age. 488 of their individual performances over nearly four decades were contrasted against a statistically generated baseline of athletes that they competed against during these events. The results indicated a relatively stable level of performance from aged 37-52 years of age. However, a noticeable decline began to take place at aged 61 which then degraded sharply at aged 70. Interestingly, the athlete did not exhibit a permanent reduction in their average velocity in their best 16.1km and 40.2km time trial performances until aged 70. This suggests that despite the physiological decline that will eventually reduce a riders competitiveness, this case study demonstrated that it is feasible to continue the pursuit of personal records until relatively late in life.